2020
DOI: 10.1016/j.ijpharm.2019.118860
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive thin films for the simultaneous delivery of microbicide and anti-inflammatory drugs in the treatment of periodontal diseases

Abstract: Changes made as a result of publishing processes such as copy-editing, formatting and page numbers may not be reflected in this version. For the definitive version of this publication, please refer to the published source. You are advised to consult the publisher's version if you wish to cite this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Goodson et al [ 60 , 65 ] were the first to come up with the idea of drug delivery in the periodontal pocket. They started with monolithic cellulose acetate fibers filled with tetracycline hydrochloride that was tied around the crevice of the pocket and then they proceeded to test other polymers, such as polyethylene, polypropylene, polycaprolactone, polyurethane, cellulose acetate propionate, and ethylene-vinyl acetate copolymer fibers [ 4 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. The researchers have observed that in case polyethylene and polyurethane, the release of the drug was very fast.…”
Section: Drug Delivery Devicesmentioning
confidence: 99%
See 3 more Smart Citations
“…Goodson et al [ 60 , 65 ] were the first to come up with the idea of drug delivery in the periodontal pocket. They started with monolithic cellulose acetate fibers filled with tetracycline hydrochloride that was tied around the crevice of the pocket and then they proceeded to test other polymers, such as polyethylene, polypropylene, polycaprolactone, polyurethane, cellulose acetate propionate, and ethylene-vinyl acetate copolymer fibers [ 4 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. The researchers have observed that in case polyethylene and polyurethane, the release of the drug was very fast.…”
Section: Drug Delivery Devicesmentioning
confidence: 99%
“…Since that time several other local drug delivery devices along with various therapeutic agents have been formulated for the effective management of periodontitis. Different types of DDS, that have been reported in recent years and a comprehensive list of all approved drugs can be found elsewhere [ 4 ]. Chitosan is also another polymer that has been investigated extensively.…”
Section: Drug Delivery Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ex vivo models such as porcine gingiva are used in some studies to evaluate anti-inflammatory effect. [23] Additional tools for FBR evaluation such as microfluidic platform were also reported: for instance, Sharifi et al developed FBR-on-a-chip (FBROC) to model the immune cell response to implants (Figure 4). The platform provides a model of the native implant microenvironment and provides a strategy to assess the FBR on various implants, in an individual and physiologically relevant manner.…”
Section: Evaluation Of Inflammatory Response To Biomaterialsmentioning
confidence: 99%